Late Palaeolithic core-reduction strategies in Dhofar, Oman - Hilbert, Yamandú H.; Rose, Jeffrey I.; Roberts, Professor Richard G. (Proceedings of the Seminar for Arabian Studies, 2012)
Systematic surveys conducted in the Dhofar Governorate of Oman have produced over 300 surface sites, as well as excavation of in situ archaeological deposits. A number of these assemblages have been classified as part of the Nejd Leptolithic Tradition (NLT). This study describes a selection of these assemblages from sites distributed across the southern and central Najd plateau in Dhofar, including both surface scatters and stratified rock shelters. The NLT is broadly characterized by the reduction of blades struck from single-platform cores with flat flaking surfaces, in conjunction with the façonnage manufacture of bifacial implements. Based on technological analysis and artefact conjoins, we distinguish three separate core reduction strategies within the NLT. Optically stimulated luminescence (OSL) dates from three in situ assemblages allow us to begin to define temporal variability within this technological continuum.